A 180° Spin of the Femoral Component in Unicompartmental Knee Arthroplasty: A Report of 2 Cases. Issue 1 (January 2022) - Bouché, Pierre-Alban; Ehkirch, François-Paul
Abstract : Case: We report 2 cases of undescribed lateral unicompartmental knee arthroplasty failure: a 180° rotation of the femoral component. The patients experienced a locking event several years after arthroplasty, and radiographs revealed a perfect 180° rotation of the implant. Each patient underwent revision surgery to a total knee arthroplasty. At the 13-year follow-up, the first patient had no pain and a range of motion of 140°. The second patient, at 3 months, could walk without crutches with a flexion at 145°. Conclusion: Excessive laxity, coronal or sagittal, might be associated with this complication.